Adsorption of Fe and Co nanowires to (3,3) single-walled carbon nanotubes - Kishi, Tomoya (Animo Repository, 2007)
We investigate the magnetic and electronic properties of Fe and Co nanowires adsorbed outside the wall of single-walled carbon nanotubes (SWNTs). We find that in Fe nanowire adsorption, the SWNT transforms into a diamond ring-like structure because of the charge transfer from the C-C bonds to the Fe-C bonds. In addition, the number of bands that crosses the Fermi level can be enhanced by adsorbing Fe and Co atoms. © 2007 The Japan Society of Applied Physics.